ISOLASI DAN IDENTIFIKASI PATOGEN GETAH KUNING MANGGIS MELALUI PENDEKATAN POSTULAT KOCH DAN ANALISIS SECARA MOLEKULER - I Ketut Suada; Ni Wayan Suniti (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
Isolation and identification of mangosteen yellow latex pathogen through Koch’s Postulate application and molecular analysis. The yellow latex disease decreases fruit quality of mangosteen because exogenic latex causes dirty fruit and the endogenic latex makes the bitter fruit taste and does not deserve to be consumed. The causal agent of the disease caused phusilogical disorder so that cells break due to unstability of cell turgor, the drift irrigation treatment was able to decrease the disease of 35.22%, therefore the causal agent could be microbe that promote the yellow latex. This research was aimed to find the yellow latex pathogens with its characteristics. The Koch Postulate was apllied to isolate and proved the microbes associated to the yellow latex and molecular analysis was constructed subsequently to find the microbe species.  The result of the research proved that there were three fungus species as the biotic agent responsible to the disease. The fungus were Verticillium albo-atrum with the highest pathogenecity ( 74.87%), followed by Fusarium oxysporum ( 70.15%), and Pestalotia macrotricha (20.32%).